Rancang Bangun Mesin Pengupas Buah Pinang - Siahaan, Derryl Gabriello; Tianur; Edilla; Hendriko (Universitas Muhammadiyah Metro, 2024)
Areca nut is classified as a grain that is widely distributed in several areas, especially Riau, especially in the Indragiri Hilir area as the largest betel nut producer in Indonesia. Peeling betel nut skin using a machine is easier and faster than manually peeling betel nut, based on that I am very interested in making a